1984
DOI: 10.1083/jcb.98.3.986
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic visualization and biochemical identification of O-phosphoserine- and O-phosphothreonine-containing phosphoproteins in mineralizing embryonic chick bone.

Abstract: We injected NaH 233P04 into normal 14-d-old embryonic chicks and examined the long bones by both radioautography and biochemical analyses from 10 to 240 min after the injection was completed . At 30 min, determination of the radiographic grain density revealed that 33p was concentrated principally in fibroblasts, preosteoblasts, and osteoblasts . With time, there was a progressive increase in the density of silver grains located over both the osteogenic cells and the regions of uncalcified (osteoid) and calcif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
9
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
(27 reference statements)
5
9
0
Order By: Relevance
“…However, following secretion, the 44 kDa OPN and most of the BSP are rapidly bound to the hydroxyapatite. This observation is consistent with autoradiographic studies in which L"P04]-labeled material synthesized by bone cells was rapidly incorporated at the mineralizing front (Leblond and Weinstock, 1976;Landis et al, 1984). Based on Fig.…”
Section: Discussionsupporting
confidence: 91%
“…However, following secretion, the 44 kDa OPN and most of the BSP are rapidly bound to the hydroxyapatite. This observation is consistent with autoradiographic studies in which L"P04]-labeled material synthesized by bone cells was rapidly incorporated at the mineralizing front (Leblond and Weinstock, 1976;Landis et al, 1984). Based on Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The results ( Table 1) show indeed that phosphoproteins were retained in the tissue during processing, including their exposure to aqueous fixative, osmium tetroxide, buffer, and acetone. The data, then, clearly confirm that the immunoreactions presented here are attributable to antigenically intact phosphoprotein preserved in the tissue by the chemical fixation and other procedures described in "Materials and Methods" and studied in earlier work (Glimcher and Kossiva, unpublished;in Landis et al, 1984). Furthermore, fixed bone tissue that was intentionally and completely decalcified in HC1 also showed retention of the majority of the phosphoprotein when compared to native, fully mineralized samples.…”
Section: Discussion Specificity Of the Lmmunolabeling Reactionsupporting
confidence: 87%
“…Intracellularly, phosphoprotein was detected in both rough endoplasmic reticulum and the Golgi apparatus of osteoblasts. These results extend previous organ culture and other studies in vivo that showed biochemically and radioautographically that bone cells synthesize and secrete phosphoproteins into the bone matrix (Glimcher et al, 1982;Gotoh et al, 1983;Landis et al, 1984;Gerstenfeld et al, 1989Gerstenfeld et al, , 1990.…”
Section: Temporal Expression and Accumulation Of Bone Phosphoproteinsupporting
confidence: 90%
See 1 more Smart Citation
“…There is uncertainty as to the biological functions of these proteins and the precise role of the covalently bound phosphate groups per se. The presence of these phosphorylated proteins in all of the normal and pathologically mineralized tissues of vertebrates, and their ultrastructural localization (17)(18)(19)(20)(21)(22)(23), have combined to suggest that one biological function of these phosphoproteins and specifically of the covalently bound phosphate groups is their critical role in the nucleation and growth of inorganic calcium-phosphate crystals (24 -26). This view is also supported by in vitro nucleation experiments, which attempted to simulate the postulated in vivo nucleation substrate of bone tissue by cross-linking the resident phosphoproteins in situ in their native positions and comparing the efficacy (induction or lag time) of this nucleation substrate with samples containing the collagen-phosphoprotein complexes after the covalent phosphate groups were enzymatically cleaved.…”
mentioning
confidence: 99%